The Implementation of AHP for Determining Dominant Criteria in Higher Education Competitiveness Development Strategy Based on Information Technology - Yulmaini, Yulmaini; Sanusi, Anuar; Yusendra, M. Ariza Eka (Universitas Dharma Wacana, 2019)
The existence of Higher Education has a huge role in nation and state’s life through tri dharma of Higher Education named education, research and community service. Higher Education can produce economic innovations based on knowledge so that, it will increase productivity and nation competitiveness. Higher Education must have strategies that will be carried out, therefore they are able to compete with other higher education according to stakeholder needs. The purposes of this research are to analyze 2 (two) models of information technology relations in the higher education competitiveness development strategy determining the most dominant criteria according to the higher education development direction (Relevance, Academic Atmosphere, Internal Management, Sustainability, Efficiency and Productivity, Access and Equit and Leadership). The method of this reserach is AHP method in wich the data are collected through questionnaires to respondents in collage. The criteria of this research are internal management & organization, academic atmosphere and university competitive sustainability. The results of this research are the information technology relations model with internal management, and the relation model between internal management and efficiency & productivities, and also the most dominant criteria in the higher education competitiveness development strategy are the criteria of Academic Atmosphere, Efficiency and Productivity.